How employee corporate social responsibility participation promotes pro-environmental behavior - Min, Yan Ai; Hao, Ma; Yang, Xiao; Ling, Deng Yu; Yuan, Jiang Si (Frontiers in Earth Science, 2024)
Urban resilience is suffering from the challenges of climate change. The increasing volatility of climate change and its impact on urban resilience necessitates a deeper understanding of how internal organizational behaviors can contribute to sustainable city development. Pro-environmental behavior is one of the important ways to affect climate change and enhance urban resilience. This study investigates the role of employee CSR participation in promoting pro-environmental behavior and its mechanism. The research was conducted in China mainland with 262 employees from various industries at two-time points. Empirical research revealed that employee CSR participation is positively related to employee pro-environmental behavior (PEB). The empirical findings are not only supported psychological ownership mediated the link between CSR participation and PEB, but also indicated employee engagement acted as an intermediary mechanism in enhancing this positive association. Moreover, the chain mediation effect of psychological ownership and employee engagement in the positive link between CSR participation and PEB was also significance. Our findings not only enriches the mechanism of CSR participation's effect on employee behavior by introducing new theoretical perspectives, but also deepens our understanding of the promoting antecedents of employee PEB, thereby contributing to the improvement of urban resilience in face with climate change.